Social Identity and Labor Market Outcomes of Internal Migrant Workers - Shu Cai; Klaus F. Zimmermann (Global Labor Organization (GLO), 2024)
Previous research on internal mobility has neglected the role of local identity contrary to studies analyzing international migration. Examining social identity and labor market outcomes in China, the country with the largest internal mobility in the world, closes the gap. Instrumental variable estimation and careful robustness checks suggest that identifying as local associates with higher migrants' hourly wages and lower hours worked, although monthly earnings seem to remain largely unchanged. Migrants with strong local identity are more likely to use local networks in job search, and to obtain jobs with higher average wages and lower average hours worked, suggesting the value of integration policies.
Keywords: J22; J31; J61; Z13; 330; assimilation; social identity; labor market; migration; internal mobility; China's Great Migration